Sexual Harassment Reconsidered: The Forgotten Grey Zone. Issue 4 (1st October 2016) - Carstensen, Gunilla
Abstract: The concept of sexual harassment in the Nordic countries and the European Union (EU) is an important tool for creating gender-equitable workplaces. This article contains an analysis of the conceptual ambiguity of sexual harassment with reference to: firstly, the lack of clarity in terms of the relation between the subjective (the perspective of the harassed individual) and the objective (legal assessment) aspects; secondly, the diffuse scope of the objective assessment; thirdly, the attribution of too much importance to the subject's perception. Even though the concept of sexual harassment classifies behaviours depending on individual interpretations, the legal construction recognizes the individual's perception in a flexible manner. If the victim does not interpret the abuse as sexual harassment, then it is not. However, if the victim does consider it sexual harassment, it will not necessarily be interpreted as such. The consequence of the three-fold ambiguity of the concept is the creation of a gender-equality grey zone. Problematic behaviours in workplaces may pass as acceptable and "normal". Subjective perception matters only when it confirms an objective incident. Defining sexual harassment in solely objective terms and determining which gender-related issues prevent equality would result in similar dilemmas, one of which would be the diminishing of those individuals who are subject to harassment. It is imperative to question the dogma that has the victim deciding whether a situation might be considered sexual harassment because: firstly, the subjective perceptions of the victim seem to be of minor importance in changing negative gender structures in workplaces; and, secondly, potential victims of harassment tend to interpret the situation as something else. Furthermore, since the current definition of sexual harassment is characterized by a preoccupation with behaviours and not with structural dimensions, the definition may actually counteract its purpose of increasing gender equality.